Performance based incentives and employees’ productivity in commercial organisations - A. M. Ogaboh Agba; T. A. Omang; C. N. Enukoha; Felix O. Eteng (Quantitative Economics and Management Studies, 2021)
The study examined the relationship between performance-based incentives and employees’ productivity in commercial organizations in Cross River State, Nigeria. Specifically, the study investigates the links between performance-based incentives such as promotions, bonus, recognition and employees’ productivity. Expectancy theory was used to situate the study. Descriptive survey design that allows for the use of questionnaire as quantitative tool was adopted as well as in the selection of respondents from commercial organizations. Quantitative data were analyzed using multi-variance analysis. It was revealed that performance-based promotion, performance-based bonus, performance-based recognition significantly influence productivity of employees in commercial organizations. The study further reveals a joint relationship between the predictor variables (performance-based promotion, bonus, recognition) and productivity of employees. It was recommended among others that promotion policies in commercial organizations should be transparent and fair. Management of these entities should make personnel policies that outline key performance indicators and their relationship to internal promotions, bonuses and wages.